Biogas production by two-stage thermophilic anaerobic co-digestion of food waste and paper waste: Effect of paper waste ratio. (March 2019) - Xiao, Benyi; Zhang, Wenzhe; Yi, Hao; Qin, Yu; Wu, Jing; Liu, Junxin; Li, Yu-You
Abstract: The effects of paper waste (PW) ratio on biogas production by two-stage thermophilic anaerobic co-digestion (coAD) of food waste (FW) and PW, two main components of organic fraction of municipal solid waste, were evaluated in lab-scale continuously stirred tank systems with semi-continuous feeding. Four PW ratios (0, 20, 40, and 50%) were studied in the test. The experimental results showed the two-stage thermophilic coAD could operate stably after an adjustment period at all PW ratios. Although the increase of PW ratio decreased methane content, production and yield, reaction rates of four AD steps, it could increase the methane production of substrate when the FW was fixed. The pH, total volatile fatty acids, total alkalinity, and total ammonium of the sludge in the second stage of AD, also decreased with the increase of PW ratio in the test. The change of the substrate's organic composition, increase of carbohydrate and decrease of protein and lipid, were the main reason for the decrease of methane content, production and yield and changes of the second stage sludge characteristics. An apposite PW ratio (PW-20%) could enhance the degradation of matters (TS, VS and TCOD). Highlights: Increase of PW ratio decrease the of biogas and methane yield of mixture. Increase of PW ratio increase the methane production when FW was fixed. Some characteristics of second stage sludge decreased with increase of PW ratio. 20% of PW ratio could enhance the degradation of matters (TS, VS and TCOD). Changes of organic composition were the main reason for experimental result.